Development of a principal approach for the transverse strength of a semi-swath vessel / Shaharudin Ahmad … [et al.] - Ahmad, Shaharudin; Abu Malik, Adi Maimun; Manurung, Yupiter Hp; Rahmad, Junaidah; Mohd Nasir, Rizal Effendy; A. Bakar, Hamzah (Research Management Institute (RMI), 2008)
Structural strength is becoming a key issue in marine transportation. A Semi-Small Water-plane Area Twin Hull (SWATH) ship is a combination of a SWATH ship and a conventional catamaran. Due to twin hull design, the strength analysis is most important especially in transverse direction to prevent from structural failure in the middle. This research are introduced an principal approach for transverse strength analysis of semi- SWATH structure; which is a supportive semiautomatic design focus on evaluate the strength of transverse Semi-SWATH bulkhead compartment beam structure under static loading. This process involves finite element modeling and verification through scale down experimental.